Dignity reflections based on experiences of end‐of‐life care during the first wave of the COVID‐19 pandemic: A qualitative inquiry among bereaved relatives in the Netherlands (the CO‐LIVE study). Issue 3 (9th October 2021) - Becqué, Yvonne N.; van der Geugten, Wendy; van der Heide, Agnes; Korfage, Ida J.; Pasman, H. Roeline W.; Onwuteaka‐Philipsen, Bregje D.; Zee, Masha; Witkamp, Erica; Goossensen, Anne
Abstract: Background: The COVID‐19 pandemic affects care practices for critically ill patients, with or without a COVID‐19 infection, and may have affected the experience of dying for patients and their relatives in the physical, psychological, social and spiritual domains. Aim: To give insight into aspects of end‐of‐life care practices that might have jeopardised or supported the dignity of the patients and their family members during the first wave of the COVID‐19 pandemic in the Netherlands. Methodology: A qualitative study involving 25 in‐depth interviews with purposively sampled bereaved relatives of patients who died during the COVID‐19 pandemic between March and July 2020 in the Netherlands. We created a dignity‐inspired framework for analysis, and used the models of Chochinov et al. and Van Gennip et al. as sensitising concepts. These focus on illness‐related aspects and the individual, relational and societal/organisational level of dignity. Results: Four themes concerning aspects of end‐of‐life care practices were identified as possibly jeopardising the dignity of patients or relatives: 'Dealing with an unknown illness', 'Being isolated', 'Restricted farewells' and 'Lack of attentiveness and communication'. The analysis showed that 'Meaningful end‐of‐life moments' and 'Compassionate professional support' contributed to the dignity of patients and their relatives. Conclusion: This study illuminates possible aspects of end‐of‐life care practices that jeopardised or supported dignity. Experienced dignity of bereaved relatives was associated with the unfamiliarity of the virus and issues associated with preventive measures. However, most aspects that had an impact on the dignity experiences of relatives were based in human action and relationships. Relatives experienced that preventive measures could be mitigated by health care professionals to make them less devastating.